2013
DOI: 10.1159/000346119
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Shunt-Dependent Chronic Hydrocephalus after Aneurysmal Subarachnoid Haemorrhage

Abstract: Introduction: Chronic hydrocephalus is a common complication that can occur after aneurysmal subarachnoid haemorrhage (SAH). The purpose of this study was to investigate clinical risk factors that could predict the occurrence of shunt-dependent chronic hydrocephalus after aneurysmal SAH. Methods: Eighty-eight consecutive patients who underwent either surgery or transarterial endovascular embolization as a treatment for cerebral aneurysm within 72 h -after experiencing SAH from March 2005 to July 2006 were stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 78 publications
2
41
0
Order By: Relevance
“…[3][4][5][6][7]11,12,16,18,23 On the basis of the evidence of an association between the severity of SAH and the prevalence of subsequent sNPH, many neurosurgeons have believed that several surgical manipulations for facilitating CSF dynamics, such as hematoma evacuation, widening the opening of the cisterns, and fenestration of the lamina terminalis, might help to reduce the subsequent occurrence of sNPH after the surgical treatment of SAH. However, the authors of a recent meta-analysis of 11 nonrandomized studies in which data from 1973 patients were pooled concluded that there was no significant difference in the prevalence of sNPH between the 975 patients who had undergone fenestration of the lamina terminalis and the 998 who had not (p = 0.09).…”
Section: 24mentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5][6][7]11,12,16,18,23 On the basis of the evidence of an association between the severity of SAH and the prevalence of subsequent sNPH, many neurosurgeons have believed that several surgical manipulations for facilitating CSF dynamics, such as hematoma evacuation, widening the opening of the cisterns, and fenestration of the lamina terminalis, might help to reduce the subsequent occurrence of sNPH after the surgical treatment of SAH. However, the authors of a recent meta-analysis of 11 nonrandomized studies in which data from 1973 patients were pooled concluded that there was no significant difference in the prevalence of sNPH between the 975 patients who had undergone fenestration of the lamina terminalis and the 998 who had not (p = 0.09).…”
Section: 24mentioning
confidence: 99%
“…The prevalence of sNPH has been reported to be 8.9%-48% in patients with SAH. [1][2][3][4][5][6][7]11,12,16,18,22,23 Acute hydrocephalus coexisting with SAH is known to be one of the most important predictors for sNPH. [3][4][5][6]11,16 Previous studies have shown that severe symptoms at SAH onset and a large amount of subarachnoid blood seen on admission CT images are associated with the development of sNPH.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While acute HC is present in 15-87 % of cases [4,6,27,33,39], chronic HC has been reported in 9-64 % of aSAH patients [2, 4-8, 19, 20, 27, 33, 36, 38, 39]. These large variations may partly be due to differences in patient cohorts, but may also relate to the fact that criteria for the use of temporary and/or permanent cerebrospinal fluid (CSF) drains differ widely between neurosurgical centers [8,22,23,26,30,35,38].…”
Section: Introductionmentioning
confidence: 99%
“…Given the risks associated with shunt surgery, proper patient selection is paramount. Even though predictors of shunt dependency such as poor clinical grade at admission, amount of subarachnoid blood, acute HC, fever frequency and mode of aneurysm repair have been identified [5,6,8,26,30,36,38], the selection of individual candidates for shunt surgery remains unclear. Some reports have also contradicted some of the predictors [15].…”
Section: Introductionmentioning
confidence: 99%